Effects of 17β-estradiol on the uterine luteolytic cascade in bovine females at the end of diestrus - Rio Feltrin, Isabella [UNESP]; Guimarães da Silva, Amanda; Rocha, Cecília Constantino; Ferraz, Priscila Assis; da Silva Rosa, Paola Maria; Martins, Thiago; Coelho da Silveira, Juliano; Oliveira, Milena Lopes; Binelli, Mario; Pugliesi, Guilherme; Membrive, Claudia Maria Bertan [UNESP] (Elsevier, 2024)
In cattle, 17β-estradiol (E2) is essential for triggering luteolysis via the synthesis of prostaglandin F2α (PGF2α). We aimed to evaluate the effects of E2-treatment on day 15 of the estrous cycle on the transcript abundance of genes involved in the PGF2α synthetic cascade. Nelore heifers (N = 50) were subjected to a hormonal protocol for the synchronization of ovulation. Between days 14 and 23 after estrus, the area (cm2) and blood perfusion (%) of the corpus luteum (CL) and progesterone (P4) plasma concentrations were evaluated daily. On day 15, the heifers were assigned to the Control (2 mL of pure sesame oil, N = 21) or Estradiol group (1 mg of E2 diluted in 2 mL of sesame oil, N = 23). After the treatments at 0 h, uterine biopsies were collected at times 1.5 h (C1.5h, N = 8 and E1.5h, N = 10) or 3 h (C3h, N = 8 and E3h, N = 11); and blood samples were obtained from 0, 3, 4, 6 and 7 h for the measurement of 13,14-dihydro-15-keto-PGF2α (PGFM) concentrations by ELISA. Transcript abundance was determined by RT-qPCR and protein abundance of ESRβ and OXTR was determined by Western Blotting. The Estradiol group showed greater (P < 0.05) concentrations of PGFM at 6 and 7 h compared to the Control group. A progressive decrease in plasma P4 concentrations characterized a hastened functional luteolysis, followed by structural luteolysis in the Estradiol group (P < 0.05). Among the treatment groups, no significant difference was detected for the abundance of PRKCα, PRKCβ, AKR1B1, PTGS2 and ESRα transcripts (P > 0.05). Estradiol treatment decreased the abundance of PLA2G4A, AKR1C4, and ESRβ both 1.5h and 3h after treatment (P < 0.05). The relative expression of PGR and OXTR was greater in E3h compared to the C3h (P > 0.05). Protein abundance did not differ between treatment groups at either experimental times (P > 0.05). Overall, E2 promoted an increase in PGFM concentrations and the hastening of functional and structural luteolysis in Nelore heifers through the upregulation of PGR and OXTR, demonstrating for the first time that the expression of these receptors within 3 h after E2 stimulus was associated with triggering luteolysis in cattle.
Keywords: Cattle; Endometrium; Estradiol; Luteolysis; Prostaglandin